KUALITAS UDARA AMBIEN, KENYAMANAN DAN KESEHATAN MASYARAKAT DI SEKITAR PABRIK GULA SEMBORO - Choiron, Choiron (FKM - UNEJ, 2011)
Industry plays an important role in the life of humanity. In the economic perspective, it is very important for states in providing numerous job vacancies for millions people worldwide. Nevertheless, activities in industrial sectors have the potential of causing air pollution. Activities ofÂ PG Semboro at a milling time have caused air condition around the factory dirty and polluted by dust from the factory smokestack. The objective of study is to describ the air quality, the comfort and health of communities living around Pabrik Gula Semboro Jember. It is a descriptive observational study conducted by using a cross sectional design. The sample is communities living at the around Pabrik Gula Semboro. Data collection is conducted by using questionnaire sheets. Result of the study indicates the ambient air quality which exceeds environmental quality standard are : dust (0,515 mg/m3) on the north side Pabrik Gula Semboro, noise (53,9-56,2 dBA) on area of Pabrik Gula Semboro, noise (50,5-61,2 dBA) on the north side Pabrik Gula Semboro. Respondents comfort disturbed byÂ odor (33%), dust (80%), noise (30%), smoke factory (26%). The community health indicates the Acute respiratory Tract Infection is the most incidence arround of Pabrik Gula Semboro. Keywords: Ambient Air quality, Comfort, Community health